KEDUDUKAN BANTUAN HUKUM DALAM SISTEM PERADILAN PIDANA DI INDONESIA - TRI LAKSONO KURNIAWAN; MIRZA AMELIA; I WAYAN PUSPA; I MADE SURADHANA (Universitas Mahasaraswati K. Mataram, 2024)
Every citizen has the same position, before the law without exception which includes the right to be defended (access to legal counsel), treated equality before the law, justice for all (justice for all). In order to seek justice, it is often only able to be accessed by those who have a high level of education and the middle to upper economic status. Recognizing that the inability of human and economic resources makes it impossible to make the process of seeking justice for underprivileged people, the term legal assistance in the Judicial System in Indonesia has emerged. The right to obtain legal assistance is a fundamental or basic right for someone who faces a legal problem, because obtaining legal assistance is one form of access to justice for those who face legal problems. This paper will discuss the state's obligations in providing legal assistance to suspects or defendants in the Criminal Justice System and the position of legal assistance in the Criminal Justice System. The method used in this paper is normative legal research, with secondary data sources consisting of primary, secondary and tertiary legal materials. Then the data is analyzed by qualitative analysis. The obligation of the state to provide legal assistance to citizens who face legal problems, because legal aid is a constitutional right of citizens. Legal assistance in the Criminal Justice System has a very important role in achieving a fair trial process. The Government has issued Law No. 16 of 2011 concerning Legal Aid, so that it can be implemented optimally to fulfill constitutional rights for the poor or needy to achieve a fair trial process.